Spectrum Of Causes Of Isolated Aortic Regurgitation At A South African Public Sector Tertiary Care Institution - Masikati, Malcolm (Department of Medicine, 2024)
BACKGROUND Aortic Regurgitation (AR) is due to primary abnormalities of the aortic valve, peri-valvular apparatus and/or the aortic root and the ascending aorta. Whereas the etiology and mechanisms of AR are relatively well described in Europe and North America, little information exists about their spectrum and frequency in sub-Saharan and South Africa. Understanding the precise mechanisms of AR informs surgical planning of valve and aorta repair. Reports from local studies suggest that rheumatic heart disease in the commonest cause of valvular heart disease in RSA particularly in population under 40 but whether it's the most common cause of isolated AR is not known. The aims of this study were to report the spectrum of causes of isolated aortic regurgitation and their distribution, including the main mechanisms of aortic regurgitation in our setting. The accuracy of pre-op assessment of etiology by clinical and imaging evaluation was also analyzed along with its concordance to surgical findings. METHODS This is a retrospective review of hospital records of patients who had aortic valve replacement (AVR) for isolated AR from Jan 2003 to June 2018 at Groote Schuur Hospital (GSH). Most patients had a presumptive etiological diagnosis determined by pre-operative echocardiography. For this study the etiology and pathological mechanism was confirmed by macroscopic examination at surgery and pathological examination of explanted valves. RESULTS There were 141 patient records available over the period. The mean age for the cohort was 43 years (range 29-57) with a male predominance of 63%. Baseline co-morbid conditions of the participants included hypertension 43.3%, Human immunodeficiency virus (HIV)16.9%, and chronic kidney disease 4.3%. The mechanistic and etiological diagnosis was available for all 141 study participants. The five predominant mechanisms were: 1- thickening/fibrosis/retraction with commissary fusion in 32.6%. 2- cusp perforation/leaflet destruction in 24.8%. 3- prolapse of the aortic leaflet cusps in 7.1%. 4- aortic root or annular dilatation in 27%. 5- Mixed mechanisms in 8.5%. The most common diseases which caused aortic regurgitation by affecting the valve leaflets were rheumatic heart disease, infective endocarditis, degenerative valve disease and bicuspid aortic valve. Diseases that affect the root and aorta included hypertension, Marfan' syndrome, syphilitic aortitis, Takayasu's arteritis; and pyogenic aortitis. Of the 141 patients in the study complete information on the pre-op echo, surgical macroscopic inspection and histological evaluation was available in 92. Of the 92 patients there was consistency in the pre and post of diagnosis in 93.5% (86/92). The most common discrepant diagnosis was rheumatic heart disease at histology or on surgical inspection but having been referred with a preoperative echo diagnosis of infective endocarditis.